Coated steel sheet for hot stamping and aqueous surface treatment liquid applicable thereto
By applying a composite coating containing tungsten, zinc, boron and other components on the AlSi coated steel plate, the friction performance and mold pollution problems caused by excessive hardness of the steel plate surface during the hot pressing process are solved, and efficient production and good performance of the steel plate after hot pressing are achieved.
Patent Information
- Application Number
- JP2024560518
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-15
- Filing Date
- 2023-04-14
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-04-14
AI Technical Summary
During the hot pressing and stamping process, the surface hardness of the AlSi coated steel plate is too high, resulting in poor friction performance, which is prone to surface damage and mold wear. At the same time, the fall of the Al-Fe alloy layer will lead to mold contamination and reduced production efficiency.
A composite coating containing water-based hydroxide polymer, tungsten content compound, zinc content compound, boron content compound and surface improver is used to form a stable composite coating through heat treatment, which improves the high-temperature friction performance of the steel plate and improves the service life of the mold.
The good high-temperature friction performance of the steel plate during hot pressing and stamping is achieved, which reduces mold wear and pollution, improves production efficiency, and maintains good welding and corrosion resistance on the steel plate after hot pressing.
Smart Images

Figure 2025513863000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of metal surface treatment, and in particular relates to coated steel sheets for hot stamping and aqueous surface treatment liquids applicable thereto. [Background technology]
[0002] Hot stamped ultra-high strength steel can reduce the weight of the car while providing the crash safety performance of the car body. It is one of the effective ways to achieve energy saving and emission reduction of the car. Therefore, hot stamped parts and hot stamping process are increasingly used in the automotive industry and are currently widely used in the manufacture of automotive parts such as A-pillars, B-pillars, door rings, center channels and bumpers.
[0003] Among plain carbon steels, only steel grades such as boron-based alloy steels can achieve a complete transformation to a martensitic microstructure during the cooling process following hot stamping formation. Of these, 22MnB5 is the most commonly used hot stamped steel. Before hot forming, this material has a ferritic-pearlitic microstructure with a yield strength of about 550 MPa. After full martensitic transformation, the yield strength can reach about 1500 MPa. To achieve a complete transformation to a martensitic microstructure, the material must undergo sufficient austenitization at high temperature, followed by hot forming and quenching to complete the phase transformation process. The austenitization treatment is carried out in a furnace, where the plate is heated to a temperature above Ac3 (typically 900-950°C) and held for 3 to 10 minutes, depending on the thickness of the plate. After full austenitization, the material is transferred from the furnace to a hot forming press. The process is carried out in air and the cooling rate must exceed 27 K / s before reaching 400° C. to ensure a diffusionless phase transformation to the martensite phase and ultimately achieve the corresponding mechanical strength.
[0004] However, when the hot stamping method is applied to boron-based alloy steel plate, the surface of the steel plate will oxidize, resulting in decarburization and the formation of scale. Decarburization reduces the surface strength of the steel plate, while scale increases the friction between the steel plate and the die, reducing the service life of the die. In addition, the scale attached to the die surface needs to be removed during production, which reduces production efficiency. Hot stamped parts require shot blasting as a post-treatment process. For parts with reduced sheet thickness, shot blasting can easily cause residual stress on the surface of the part, leading to deformation. In addition, for parts that require corrosion resistance, post-processing steps such as surface cleaning, surface pretreatment and application of anti-rust coating are required, which reduces production efficiency.
[0005] In order to prevent oxidation and decarburization on the surface of steel sheets and to improve the high temperature resistance and corrosion resistance of hot stamped steel sheets, high temperature oxidation prevention technologies applicable to hot stamped steel sheets have been developed. These mainly include hot dip aluminizing with aluminum-silicon (Al-10 wt%Si), pure zinc (GI), alloy zinc-iron (GA) and electroplating zinc-nickel (Zn-11 wt%Ni) coatings as well as multi-functional protective coatings, etc. However, the heating temperature (700-1000°C) during hot pressing is higher than the melting and boiling points of Zn metal and alloys, leading to embrittlement induced by liquid metal (Zn or Zn-Fe) (liquid metal induced embrittlement), which limits the use of GI and GA coatings. Although Zn-Ni coatings have certain application prospects, they are expensive and have low productivity. Although antioxidant oils, protective coatings, etc. can prevent high temperature oxidation of steel sheet substrates to a certain extent, they suffer from poor surface adhesion and uniformity when exposed to high temperatures, and the surface This leads to powdering and spalling of the coating, lack of corrosion resistance, and narrow welding windows.
[0006] Aluminum silicon (AlSi) coating has the characteristics of no oxide scale spalling during heating, no need for sandblasting after stamping, high forming accuracy, no need for nitrogen protection, and large welding window after heating. Therefore, it is currently widely used in hot stamping process. In addition, AlSi coating also has a certain anti-rust effect, which improves corrosion resistance. However, during the heating process of steel plate with AlSi coating on the surface, element Fe from the steel plate diffuses into the AlSi coating to produce various Al-Fe-Si layers and Al-Fe alloy layers in the bulk phase and on the surface of the AlSi coating. Among them, the Al-Fe alloy layer has extremely high hardness, which may lead to surface damage and wear problems on both the processed parts and the die due to the contact and friction between the AlSi coated steel plate and the die during the hot stamping process.
[0007] Due to the high surface hardness of the Al-Fe alloy layer, it is difficult to achieve relative sliding at high temperatures, resulting in poor lubrication. During the hot stamping process, it is prone to cracking, and in places with large deformation, defects such as cracks perpendicular to the interface between the coating and the iron substrate may appear, and the surface may be powdered, leading to reduced formability of the steel sheet. In addition, the peeled Al-Fe metal compounds adhere to the die, which further deteriorates the friction between the coated steel sheet and the die, thereby reducing the quality of the final part and causing wear on the die surface. As a result, more frequent die repairs are required to remove the Al-Fe metal compounds adhered to the die surface, resulting in reduced production efficiency and increased production costs for the finished parts.
[0008] Therefore, in order to prevent damage to the surface of the parts and the mold during the hot stamping process of the steel sheet coated with an AlSi layer, while also reducing the adhesion of the Al-Fe metal compound onto the mold surface, Publication No. CN102066615A provides a solution of forming a surface coating layer containing ZnO with a wurtzite crystal structure on the Al plating layer, so that the Al plating layer has lubricity, can prevent the plating thickness from becoming uneven during heating, and improve the formability of the hot stamped steel sheet. However, in this technology, the ZnO particles need to be adhered to the surface of the Al plating layer using adhesives such as organic resins and silane coupling agents. These adhesives will be oxidized and decomposed at a heating temperature of 700-1000°C, causing a large amount of ZnO to peel off from the surface of the Al plating layer. During this process, the peeled ZnO particles may diffuse and contaminate the furnace channel during the heating process, or adhere to the mold surface during the hot stamping process, thereby causing mold contamination. Furthermore, residual ZnO particles on the surface of the aluminized layer can deteriorate the weldability of the formed parts.
[0009] Publication No. CN104093880A discloses a solution containing at least one Zn compound selected from the group consisting of Zn hydroxide, Zn phosphate, and Zn organic acid as a surface coating layer on the Al plating layer. This technology also requires at least one of organic resin, silane coupling agent, and silica sol as an adhesive. However, Zn hydroxide, Zn phosphate, and Zn organic acid are all oxidized to zinc oxide (ZnO) at a heating temperature of 700-1000°C, and the above-mentioned adhesives may also oxidize and decompose. Therefore, similar to the technology of CN102066615A mentioned above, this technology also does not address the problem of poor adhesion of Zn-containing oxide particles on the Al plating layer surface after hot stamping, as well as the problem of peeled Zn oxide particles contaminating the furnace channel and mold.
[0010] Publication No. CN104220641A discloses the addition of a compound containing one or more transition metal elements as an additive for improving lubricity in a surface coating layer containing ZnO. However, like the two above mentioned patents, this technology also requires an organic adhesive to aid in the film formation and adhesion of ZnO and transition metal compounds. After the organic adhesive decomposes under heating conditions of 700-1000°C, it is also impossible to maintain the adhesion of ZnO and transition metal compounds on the surface of the aluminum plating layer of the steel sheet.
[0011] Publication No. CN105121691A discloses that a steel sheet can improve its heating performance in hot pressing by including an Al plating layer containing 0.02 to 2 mass% of one or more elements selected from Mg, Ca, Sr, Li, Na, and K, and a surface coating layer containing ZnO laminated on the Al plating layer. However, changing the composition of the Al plating layer also does not solve the problem that after the ZnO surface coating layer containing an organic adhesive is heated at 700 to 1000°C, the ZnO cannot form an effective bond on the surface of the Al plating layer due to the decomposition of the adhesive.
[0012] Publication No. CN107636200A provides a surface treatment solution for hot-pressed plated steel sheet, which includes ZnO aqueous dispersion and water-dispersible organic resin, where the water-dispersible organic resin acts as a film-forming adhesive after the surface treatment solution is applied to the surface of the plated steel sheet and dried to form a film. From the processing procedure of hot-pressed steel sheet: under the heating condition of 700-1000℃, it can be seen that after the organic resin is decomposed due to high temperature, the ZnO particles cannot form effective adhesion on the surface of the plated layer, as in the above-mentioned technology.
[0013] In summary, the technology of applying wurtzite ZnO particles and water-based resin on the surface of Al or AlSi plating layer to improve thermal lubricity and chemical conversion processability has a certain effect. However, for water-based resin, thermal decomposition occurs under high-temperature heat treatment conditions, so that a large number of ZnO particles cannot form effective adhesion on the surface of the plating layer. As a result, the coating often needs more than 3 g / m to show obvious thermal lubricity. 2 However, it requires higher coating weight, such as wurtzite ZnO compound with more than 100%. The advantages in thermal lubricity, chemical conversion processability after hot forming, and the corresponding improvement in coating corrosion resistance shown in practical situations are also unstable. In addition, the use of other adhesives such as silane coupling agents cannot solve the problem of reduced adhesion of the coating layer due to the decomposition of the adhesive after high-temperature heat treatment. It also introduces thermal decomposition products such as silica, which will harm the welding performance, adhesion performance and chemical conversion processability during coating, as well as affect the adhesion and corrosion resistance of the coating after coating. Summary of the Invention
[0014] In view of the above-mentioned shortcomings existing in the prior art, the object of the present invention is to provide a coated steel sheet for hot stamping and an aqueous surface treatment liquid applicable thereto.
[0015] In the present invention, by designing the composition of the aqueous surface treatment liquid and applying it on the surface of the coated steel sheet, the hot stamping coated steel sheet has good high-temperature lubricity during the hot stamping process, the workability of the hot stamping coated steel sheet is improved, the wear of the surface of the hot stamping die is reduced, the frequency of die repair is reduced, and the production efficiency is improved. Furthermore, after the hot stamping coated steel sheet is hot stamped, it can achieve good weldability and adhesion, good chemical conversion processability, and improved corrosion resistance after coating.
[0016] Specifically, the present invention adopts the following technical solutions:
[0017] According to a first aspect of the present invention, there is provided a coated steel sheet for hot stamping, comprising a coated steel sheet and a composite coating layer formed by applying an aqueous surface treatment liquid onto the coated steel sheet; Here, the coated steel sheet is a substrate and an Al or A film disposed on one or both sides of the substrate. lSi-containing coating; The composite coating layer contains an aqueous anionic polymer resin A, a tungsten-containing compound B, a zinc-containing compound C, a boron-containing compound D, a water-soluble thickener E and an aqueous surface improvement aid F.
[0018] Preferably, the composite coating layer has a thickness of 1 to 5 g / m 2 The dry film weight is
[0019] According to a second aspect of the present invention, there is provided an aqueous surface treatment solution for forming the above-mentioned composite coating layer on a coated steel sheet, wherein the aqueous surface treatment solution is formed by dispersing a solid phase material in water; wherein the solid phase material comprises the following components in parts by weight: Aqueous anionic polymer resin A: 15-65 parts; Tungsten-containing compound B: 10 to 40 parts by mass of tungsten element; Zinc-containing compound C: 3 to 15 parts by mass of zinc element; Boron-containing compound D: 0.004 to 0.03 parts by mass of boron element; Water-soluble thickener E: 0.01 to 0.5 parts; Aqueous surface improvement aid F: 0.5 to 2 parts.
[0020] Preferably, the aqueous anionic polymer resin A is one or more selected from aqueous acrylic resins, aqueous epoxy resins, aqueous polyester resins and aqueous alkyd resins; and / or the tungsten-containing compound B is one or more selected from tungsten oxide, tungstate or tungsten metal salt; and / or the zinc-containing compound C is selected from zinc oxide, a zinc salt or an organozinc compound; and / or the boron-containing compound D is selected from boron oxide, a borate or an organoboron compound; and / or the water-soluble thickener E is one or more selected from water-soluble hydroxymethylcellulose, water-dispersible alkali-swellable polyacrylic acid emulsion, water-dispersible non-ionic polyurethane associative thickening resin; and / or The aqueous surface improvement aid F is one or two selected from water-dispersible modified polydimethylsiloxane and water-dispersible polyether modified silicone; and / or wherein the aqueous anionic polymer resin A is 20 to 50 parts by mass; and / or The tungsten-containing compound B is present in an amount of 15 to 35 parts by mass in terms of parts by mass of tungsten element.
[0021] Preferably, the aqueous anionic polymer resin A has a number average molecular weight greater than 8,000 and the mass fraction of harmful substances resulting from the combustion of the aqueous anionic polymer resin A is less than 1% by weight of the total solids of the aqueous anionic polymer resin A; and / or When tungsten-containing compound B is a water-insoluble tungsten compound, the tungsten-containing compound B has a particle size of 5 to 1,000 nm; and / or When the zinc-containing compound C is a water-insoluble zinc compound, the zinc-containing compound C has a particle size of 5 to 1,000 nm; and / or the mass ratio of elemental zinc in said zinc-containing compound C to elemental boron in said boron-containing compound D is from 150:1 to 750:1, preferably from 250:1 to 670:1; and / or The water-soluble thickener E has a number average molecular weight of 50,000 to 100,000.
[0022] Preferably, the tungsten-containing compound B has a particle size of 20 to 500 nm; and / or The zinc-containing compound C has a particle size of 20 to 500 nm.
[0023] According to a third aspect of the present invention, there is provided a manufacturing method for the above-mentioned coated steel sheet for hot stamping, comprising the following steps: applying an aqueous surface treatment liquid onto a surface-cleaned Al or AlSi coated steel sheet, and then curing the aqueous surface treatment liquid at 80-180°C to form a composite coating layer on the Al or AlSi coated steel sheet, thereby obtaining a coated steel sheet for hot stamping.
[0024] According to a fourth aspect of the present invention, there is provided a hot stamping method for the coated steel sheet for hot stamping described above, comprising the steps of cutting the coated steel sheet for hot stamping into a die, heating and stamp forming.
[0025] Preferably, during the heating process, the hot stamping coated steel sheet cut into a mold is heated from 50°C to the final plate temperature and held for 30-60 seconds; then the heated hot stamping coated steel sheet is transferred to a stamp forming mold having a cooling effect.
[0026] Preferably, during the heating process, the average heating rate is between 3 and 12°C / s and the reached plate temperature is between 850 and 980°C; and / or The stamp forming process is carried out in air with a cooling rate of ≧27° C. / s before the temperature of the hot stamping coated steel sheet is reduced to 400° C. The method of cooling the steel sheet is as follows: the stamp forming die has a water cooling function. During hot stamp forming, the cooling rate is controlled by adjusting the flow rate of the cooling water in the die and the pressure holding time. Alternatively, forced cooling can be carried out by water mist spraying, provided that the cooling rate meets the requirements. There is no special limit on the upper limit of the cooling rate, which can be selected according to actual needs. Considering the process cost, it is preferable to set the upper limit of the cooling rate at 50° C. / s.
[0027] According to a fifth aspect of the present invention, there is provided a hot stamped formed coated steel sheet obtainable by the hot stamping method described above, wherein the hot stamped formed coated steel sheet has a yield strength of ≥ 950 MPa, a tensile strength of ≥ 1300 MPa, an elongation after break A of ≥ 5%. 50mm , hardness HV10 of ≧400 or hardness HRC of ≧40, and cold bending angle VDA of ≧45°. The coated steel sheet for hot stamping and the aqueous surface treatment liquid applicable thereto provided by the present invention have the following beneficial effects:
[0028] 1. In the present invention, by designing the composition of the aqueous surface treatment liquid and applying it on the surface of the coated steel sheet, the hot stamping coated steel sheet has good high-temperature lubricity during the hot stamping process, the processability of the hot stamping coated steel sheet is improved, the wear of the surface of the hot stamping die is reduced, the frequency of die repair is reduced, and the production efficiency is improved. Furthermore, after the hot stamping coated steel sheet is hot stamped, it can achieve good weldability and adhesion, good chemical conversion processability, and improved corrosion resistance after coating.
[0029] 2. The present invention provides Al or AlSi coated steel sheet for hot forming and an aqueous surface treatment liquid. The aqueous surface treatment liquid and the products treated therewith do not contain harmful elements such as chromium and have little impact on the environment.
[0030] 3. The coated steel sheet for hot stamping of the present invention is coated on its surface with a composite coating layer containing tungsten (W), zinc (Zn) and an organic resin. The composite coating layer has an anticorrosive effect equivalent to that of anticorrosive oil and can withstand long-term transportation or storage without the protection of anticorrosive oil. In addition, the coated steel sheet for hot stamping has stable thermal lubricity during the hot stamping process, as well as good chemical conversion processability, corrosion resistance after coating, and spot welding performance after hot stamping.
[0031] 4. The aqueous surface treatment solution of the present invention is easy to apply and has stable performance.
[0032] 5. The manufacturing method and hot stamping method for the coated steel sheet for hot stamping of the present invention have a short process flow and are easy to carry out. [Brief description of the drawings]
[0033] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments, taken in conjunction with the accompanying drawings, in which: [Figure 1] FIG. 1 is a schematic diagram of the structure of the coated steel sheet for hot stamping of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a testing machine for testing the high-temperature friction coefficient of a strip in one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic longitudinal cross-sectional view of a sample plate of the adhesive component used to test the adhesion.
[0034] Reference List 10 Substrate 11 Al or AlSi-containing coating 12 Composite coating layer 20 Test sample plate 21 Motor 22 Coupling 23 Transmission shaft 24 Recorder 25 Force Sensor 26 Upper mold 27 Cooling Water Channel 28 Lower mold 29 Heating Furnace DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Detailed Description of the Preferred Embodiments In order to better understand the above technical solutions of the present invention, the present invention will be further illustrated in combination with the following examples.
[0036] As shown in Figure 1, the present invention provides a coated steel sheet for hot stamping, which includes a coated steel sheet and a composite coating layer 12 formed by applying an aqueous surface treatment liquid onto the coated steel sheet; wherein the coated steel sheet includes a substrate 10 and an Al or AlSi-containing coating 11 disposed on one or both sides of the substrate 10. The composite coating layer 12 contains an aqueous anionic polymer resin A, a tungsten-containing compound B, a zinc-containing compound C, a boron-containing compound D, a water-soluble thickener E and an aqueous surface improvement assistant F.
[0037] The composite coating layer 12 has a thickness of 1 to 5 g / m 2 That is, the thickness of the composite coating layer 12 on each side is 1 g / m 2 and 5g / m 2 The reason is as follows: When the coating weight of the composite coating layer is 1 g / m 2 When the coating weight of the composite coating layer 12 is less than 5 g / m2, the low coating weight leads to a decrease in the processing lubrication function of the steel sheet during hot stamp forming. 2 On the other hand, when the surface treatment cost per unit area of the steel plate exceeds on the other hand, an excessively thick coating layer may cause the organic components in the composite coating layer 12 to be unable to be completely decomposed during the heat treatment process, and some inorganic materials in the coating layer may not form good adhesion with the surface of the Al or AlSi coated steel plate, and the residues from the combustion of the inorganic materials may contaminate the furnace and the mold.
[0038] The mass parts of each solid component in the composite coating layer 12 are as follows: aqueous anionic polymer resin A: 15 to 65 parts; tungsten-containing compound B: 10 to 40 parts by mass of elemental tungsten; zinc-containing compound C: 3 to 15 parts by mass of elemental zinc; boron-containing compound D: 0.004 to 0.03 parts by mass of elemental boron; water-soluble thickener E: 0.01 to 0.5 parts; aqueous surface improvement assistant F: 0.5 to 2 parts.
[0039] The aqueous anionic polymer resin A is one or more composite resins selected from aqueous acrylic resins, aqueous epoxy resins, aqueous polyester resins and aqueous alkyd resins. The aqueous anionic polymer resin A should have a number average molecular weight greater than 8,000. The mass fraction of harmful nitrogen, sulfur and chlorine elements that may be generated from the combustion of the aqueous anionic polymer resin A should be less than 1% by weight of the total solid content of the aqueous anionic polymer resin A. The aqueous anionic polymer resin A can be dispersed in water in the form of an aqueous solution, an aqueous dispersion or an emulsion type.
[0040] The composite coating layer 12 contains 15-65 parts by weight of the aqueous anionic polymer resin A. When the weight part of the aqueous anionic polymer resin A is less than 15 parts, the adhesion of the composite coating layer formed by the aqueous anionic polymer resin A on the surface of the hot stamping Al or AlSi coated steel sheet may be reduced. When the weight part of the aqueous anionic polymer resin A is more than 65 parts by weight, the relative ratio of the tungsten-containing compound B, which mainly plays a role of high temperature lubrication in the composite coating layer on the surface of the hot stamping Al plated or AlSi plated steel sheet, may be reduced, and sufficient lubrication may not be provided during the hot stamping process. More preferably, the composite coating layer 12 contains 20-50 parts by weight of the aqueous anionic polymer resin A.
[0041] The tungsten-containing compound B has a high-temperature lubricating function, and its mass part as tungsten element is 10-40 parts. The reason is as follows. When the mass part as tungsten element of the tungsten-containing compound B having high-temperature lubricating function is less than 10 parts, it cannot play the role of high-temperature lubrication. When the mass part as tungsten element of the tungsten-containing compound B having high-temperature lubricating function is more than 40 parts, the performance of the composite coating layer is deteriorated, which may affect the properties such as adhesion, water resistance and corrosion resistance of the coating and Al or AlSi coated steel plate, and may increase the production cost. Preferably, the mass part as tungsten element of the tungsten-containing compound B having high-temperature lubricating function is 15-35 parts.
[0042] Preferably, the tungsten-containing compound B with high temperature lubricating function is formed during the hot stamping process and contains compounds with lubricating function such as tungsten oxide and tungstate. When the tungsten-containing compound B is coated on Al or AlSi-based coated steel plate, it has a lubricating effect at the interface between the steel plate and the mold. The source of the tungsten-containing compound B is tungsten trioxide (WO3), tungsten dioxide (WO2) or blue tungsten oxide (WO 2.72 , WO 2.90 , W 20 O 58 and (NH4) x tungsten oxide, such as tungsten oxide (WO3); or sodium tungstate (Na2WO4), potassium tungstate (K2WO4), lithium tungstate (Li2WO4), magnesium tungstate (MgWO4), calcium tungstate (CaWO4), cobalt tungstate (CoWO4), cadmium tungstate (CdWO4), ferrous tungstate (FeWO4), ammonium tungstate Um[(NH4)6W7O 24 ] and zinc tungstate (5ZnO·12WO3); or tungsten metal salts, such as tungsten chloride [tungsten hexachloride (WCl6), tungsten pentachloride (WCl5), tungsten tetrachloride (WCl4), tungsten dichloride (WCl2)]; or other types of tungsten-containing compounds, such as nano-tungsten carbide (WC), tungsten disulfide (WS2) and tungsten diselenide (WSe2). The tungsten-containing compound B with high-temperature lubrication function may contain one or more tungsten oxides, tungstates, tungsten salts or other tungsten-containing compounds. These may be the same type of tungsten oxides, tungstates, tungsten salts or other tungsten-containing compounds, or they may be different types of tungsten oxides, tungstates, tungsten salts, other tungsten-containing compounds, or mixtures thereof.
[0043] Tungsten-containing compound B, which has high-temperature lubrication function, undergoes thermal decomposition and thermochemical reaction during hot stamping and heating process (limit temperature reaches 850℃~980℃). Therefore, from the viewpoint of environmental protection and operation safety, tungsten-containing compound that decomposes at high temperature and produces harmful substances should be avoided. Preferably, tungsten-containing compound B is tungsten trioxide (WO3), sodium tungstate (Na2WO4), potassium tungstate (K2WO4), magnesium tungstate (MgWO4), ammonium tungstate [(NH4)6W7O 24 and nano-tungsten carbide (WC).
[0044] The tungsten-containing compound B having high temperature lubricating function can be uniformly dispersed in the composite coating layer 12 in the form of powder or solute. Preferably, in order to improve the dispersibility of the tungsten-containing compound B having high temperature lubricating function, the aqueous anionic polymer resin A having good compatibility with it can be selected to match it. For the tungsten-containing compound B in powder form, a dispersant can be added in an amount of 0.01 to 0.5 parts by mass to improve the dispersibility of the tungsten-containing compound B in the aqueous anionic polymer resin A matrix, so that the tungsten-containing compound B having high temperature lubricating function maintains basic stability in physical properties below 200 ° C and does not aggregate or separate in the composite coating layer 12.
[0045] The tungsten-containing compound B having high-temperature lubricating function, such as tungsten oxide, tungstate, tungsten salt or other tungsten-containing compound insoluble in water, has a particle size of 5-1000 nm, preferably 20-500 nm in powder form.
[0046] The tungsten-containing compound B with high-temperature lubrication function is a suitable high-temperature lubrication auxiliary in the hot stamping process. This is because the tungsten-containing compound B, such as tungsten oxide, tungstate, tungsten salt or other tungsten-containing compounds, can partially or completely decompose (or transform) into tungsten oxide (WOx), which is a solid lubricant with high ionic potential at high temperature. For example, tungstate can undergo a substitution reaction with Al2O3 on the surface of Al or AlSi coating at high temperature:
[0047] [ka]
[0048] Upon receiving the above reaction, WO3 with high temperature lubrication function can be formed. The formed tungsten oxide shows good adhesion to Al or AlSi coating at high temperature. In addition, zinc tungstate (5ZnO·12WO3), nano tungsten carbide (WC), tungsten disulfide (WS2), tungsten diselenide (WSe2), etc. also have good high temperature oxidation resistance and high temperature lubrication properties by themselves.
[0049] The mass parts of the zinc-containing compound C as zinc element is 3-15 parts. The reason is as follows. When the mass parts of the zinc-containing compound C as zinc element is less than 3 parts, it cannot effectively improve the chemical conversion processability of the part after hot forming and the corrosion resistance after coating. When the mass parts of the zinc-containing compound C as zinc element is more than 15 parts, it may lead to reduced adhesion between the surface composite coating and the Al or AlSi coated steel sheet, and the zinc-containing conversion layer formed after hot forming may not adhere well to the surface of the coated steel sheet. When the zinc-containing compound C is a zinc-containing compound that is insoluble in water, in order to ensure its uniform dispersion in the surface composite coating layer, its particle size in powder form should be 5-1000 nm, preferably 20-500 nm. The source of the zinc-containing compound C can be zinc oxide, such as zinc oxide (ZnO); zinc salts, such as zinc nitrate (ZnNO3) and zinc chloride (ZnCl2); or zinc acetate (Zn(Ac)2) and zinc stearate (C 36 H 70 The compound may be an organozinc compound, such as ZnO.
[0050] The mass part of the boron-containing compound D as elemental boron is 0.004-0.03 parts. The reason is as follows. When the mass part of the boron compound D as elemental boron is less than 0.004, it cannot effectively improve the adhesion of the coating to the surface of the Al or AlSi coated steel sheet after hot forming. When the mass part of the boron compound D as elemental boron is more than 0.03, the reactivity of the composite coating layer with the chemical treatment agent and the coating performance after hot forming will be deteriorated. The source of the boron-containing compound D can be boron oxide, such as boron oxide (B2O3); borate, such as magnesium borate (MgHBO3), sodium tetraborate (Na2B4O7) and sodium borohydride (NaBH4); or organic boron compounds, such as borane, carborane, methyl borate and organic borates.
[0051] The mass ratio of zinc-containing compound C as elemental zinc to boron-containing compound D as elemental boron (W Zn / W B) is 150:1 to 750:1. The boron-containing compound D is a suitable adhesion promoter in the hot forming process because boron oxide, borate or organic boron compound can decompose to B2O3 under heat treatment. B2O3 functions as a flux and network former, and when combined with the zinc-containing compound C, forms a zinc borate (e.g., B2O6Zn3) solid solution, which improves the adhesion of the surface composite coating layer to the surface of the Al or AlSi-based coated steel sheet after hot forming.
[0052] The amount of water-soluble thickener E to be added is 0.01 to 0.5 parts. The reason is as follows: when the mass part of the water-soluble thickener is less than 0.01 parts, it has no obvious thickening effect. When the mass part of the water-soluble thickener is more than 0.5 parts, it is very likely to bring about poor uniformity of the surface composite coating layer on the surface of the Al or AlSi-based coated steel plate, and deteriorate the leveling of the aqueous surface treatment liquid after coating.
[0053] The water-soluble thickener E is one or more selected from water-soluble hydroxymethylcellulose, water-dispersible alkali-swellable polyacrylic acid emulsion, and water-dispersible nonionic polyurethane associative thickening resin. The number average molecular weight of the water-soluble thickener E (such as water-soluble hydroxymethylcellulose, water-dispersible alkali-swellable polyacrylic acid emulsion, and water-dispersible nonionic polyurethane associative thickening resin) is 50,000 to 100,000.
[0054] The amount of the aqueous surface improvement assistant F to be added is 0.5-2 parts. The reason is as follows. When the mass part of the aqueous surface improvement assistant is less than 0.5 parts, the aqueous surface treatment liquid cannot play a good spreading and leveling role on the surface of the Al or AlSi-based coated steel sheet, and cannot form a sufficiently spreading and uniform composite coating layer on the surface of the Al or AlSi-based coated steel sheet. When the mass part of the aqueous surface improvement assistant is more than 2 parts, it is very likely to cause defects such as cissing and pinholes occurring during the drying process of the aqueous surface treatment liquid after coating.
[0055] Water-based surface improvement aid F is a water-dispersible modified polydimethylsiloxane and a water-dispersible polyether. and terephthalic acid-modified silicones.
[0056] The above-mentioned aqueous surface treatment liquid is applied to an Al or AlSi coated steel sheet whose surface has been cleaned, and the aqueous surface treatment liquid is solidified at 80-180°C to form a composite coating layer on the Al or AlSi coated steel sheet, thereby obtaining a coated steel sheet for hot stamping. The Al or AlSi coated steel sheet having the composite coating layer on its surface obtained by the above-mentioned method has excellent hot stamping workability, excellent weldability after formation, and good coatability. Methods for applying the aqueous surface treatment liquid onto the Al or AlSi coated steel sheet include roller coating, dipping, or spraying. The aqueous surface treatment liquid may be applied to one or both sides of the Al or AlSi coated steel sheet.
[0057] The reason why the surface treatment liquid solidifies at 80-200°C is as follows. At 80-180°C, the water and water-soluble low-boiling additives, which are the solvents in the aqueous surface treatment liquid, can evaporate, promoting the crosslinking and film formation of the aqueous anionic polymer resin A. When the curing temperature is lower than 80°C, the dry film of the composite coating layer formed by the aqueous surface treatment liquid and the Al or AlSi coated steel plate is not completely crosslinked, which may lead to a decrease in the adhesive strength of the dry film. When the curing temperature is higher than 180°C, on the one hand, the surface treatment energy cost of the steel plate will increase, and on the other hand, the performance of a part of the composite coating layer will change, thereby adversely affecting the dry film of the composite coating layer. In the present invention, there is no particular strict restriction on the heating and drying method of the aqueous surface treatment liquid coated on the surface of the Al or AlSi coated steel plate. The heating and drying method can be various heating methods such as hot air heating, induction heating and infrared heating.
[0058] The present invention also provides a method for hot stamping a coated steel sheet for hot stamping, comprising the steps of cutting either an Al or AlSi coated steel sheet for hot stamping having the above-mentioned composite coating layer on its surface into a die, heating and stamp forming. During the heating process, the cut-out coated steel sheet for hot stamping is heated from 50°C to a final sheet temperature and held for 30-60 seconds; then the heated coated steel sheet for hot stamping is transferred to a stamp forming die having a cooling effect. During the heating process, the average heating rate is 3-12°C / s, and the final sheet temperature is 850-980°C; the stamp forming process is carried out in air with a cooling rate of ≧27°C / s before the temperature of the coated steel sheet for hot stamping is reduced to 400°C.
[0059] The coated steel sheet for hot stamping and the aqueous surface treatment liquid of the present invention will be further described below in combination with specific examples / embodiments. EXAMPLES
[0060] Examples 1 to 32 and Comparative Examples 1 to 8 In Examples 1 to 32 and Comparative Examples 1 to 8, the substrates were all molten aluminum silicon (AlSi) alloy-coated steel sheets. The aqueous surface treatment liquid was applied onto the surface of the cleaned AlSi alloy-coated steel sheet and dried at 80 to 180°C to obtain a coating of 1 to 5 g / m 2 A composite coating layer having a dry coating weight of was formed on the surface of the AlSi alloy coated steel plate.
[0061] The selected steel sheet is preferably subjected to a hot stamp forming process to result in steel sheets with various strength levels, including various properties related to mechanical deformation and fracture characteristics, such as tensile strength, yield strength, elongation after break, hardness, cold bending angle, etc. In one embodiment of the present invention, after hot stamping, the steel sheets have a yield strength of ≥ 950 MPa, a tensile strength of ≥ 1300 MPa, and an elongation after break of ≥ 5% (A 50mm), hardness HV10≧400 (or HRC≧40) and cold bending angle VDA(1.4mm)≧45° are selected. There are no special restrictions on the upper limit of the performance of the coated steel sheet after hot stamping. Of course, the steel Taking into consideration the production costs of the plate comprehensively, for the coated steel plate after hot stamping forming, the upper limit of the yield strength can be set to 1200MPa, the upper limit of the tensile strength can be set to 1500MPa, the upper limit of the elongation after break can be set to 10%, the upper limit of the hardness HV10 can be set to 500, the upper limit of the HRC can be set to 50, and the upper limit of the cold bending angle VDA can be set to 80°.
[0062] The above mechanical properties (including yield strength, tensile strength, and elongation after break) are in accordance with GB / T 228.1-2010 “Metallic materials - Tensile testing - Part 1: Method of test at room temperature The hardness HV10 of coated steel sheets is measured according to GB / T 4340-2012 “Metallic materials - Vickers hardness test”. Rockwell hardness HRC is measured according to GB / T 230-2018 “Metallic materials - Rockwell The cold bending angle VDA is measured in accordance with the VDA238-100 standard.
[0063] The chemical composition of the steel plate, in mass%, is carbon (C): 0.20-0.25 wt%, silicon (Si): 0.01-0.4 wt%, manganese (Mn): 1.0-1.4 wt%, titanium (Ti): 0.02-0.05 wt%, boron (B): 0.001-0.005 wt%, with the remainder being Fe and other unavoidable impurities.
[0064] In steel plates, the addition of C ensures the mechanical strength of the steel plate. When the C content is less than 0.2 wt%, the above-mentioned yield strength and tensile strength cannot be obtained. On the other hand, when the C content exceeds 0.25 wt%, the steel plate can be harder, but the melt cracks are more likely to occur. Cracks easily occur during hot stamping, resulting in a decrease in elongation at break and cold bending angle performance. Therefore, the C content is preferably 0.20-0.25 wt%.
[0065] Si and C are also elements that ensure the mechanical strength of the steel sheet. When the Si content is less than 0.01 wt%, the effect of enhancing the mechanical strength is not shown, and the above-mentioned yield strength and tensile strength cannot be obtained. On the other hand, Si is an element that is easily oxidized. When the Si content exceeds 0.4 wt%, the surface energy of the steel sheet will be reduced, and the wettability during hot-dip plating will be affected, resulting in incomplete plating or no plating. Therefore, the Si content is preferably 0.01-0.4 wt%.
[0066] Mn is an element that improves the hardenability and strength of the steel sheet after hot stamping. In addition, Mn reacts with sulfur (S), an impurity element, to form manganese sulfide (MnS), which prevents the steel sheet from developing hot embrittlement due to sulfur (S). When the Mn content is less than 1.0 wt%, the desired yield strength and tensile strength cannot be obtained. On the other hand, when the Mn content is more than 1.4 wt%, the excess remaining γ phase after hot stamping may lead to a decrease in yield strength and tensile strength. Therefore, the Mn content is preferably 1.0-1.4 wt%.
[0067] Ti can improve the strength of steel plate and improve the heat resistance of Al-based coating. When the Ti content is less than 0.02 wt%, the effect of improving mechanical strength and oxidation resistance cannot be obtained. On the other hand, when the Ti content is higher than 0.05 wt%, the excess Ti is prone to generate carbides and nitrides that soften the steel with elements such as C and N, and there is a high possibility that the desired yield strength and tensile strength cannot be obtained. Therefore, the Ti content is preferably 0.02-0.05 wt%.
[0068] B is an element that plays a role in improving the mechanical strength of steel plate during the quenching process. When the B content is less than 0.001 wt%, there is no effect of improving the strength after quenching, and the desired yield strength and tensile strength cannot be obtained. On the other hand, when the B content is more than 0.005 wt%, the rolling load during hot rolling increases significantly, and inclusions are easily generated in the steel plate, which may embrittle the steel plate and reduce the fatigue strength of the steel plate. Therefore, the B content is preferably 0.001-0.005 wt%.
[0069] Furthermore, the above-mentioned component composition of the pre-coated steel sheet (substrate) is merely exemplary. The substrate of the present invention may also contain other components. For example, the substrate may also contain deoxidizing elements such as 0.01-0.06 wt% aluminum (Al) and 0.01-0.35 wt% chromium (Cr). Al and Cr have the same effect as Mn, and also have the effect of improving the hardenability of the steel sheet. Furthermore, the steel sheet also contains inevitable impurities introduced in the manufacturing process.
[0070] The Al or AlSi coating is formed on one or both sides of the substrate mentioned above. In this embodiment, the Al or AlSi coating is formed on one or both sides of the substrate by a hot-dip coating method, but it is not limited to such a coating method. The function of the Al or AlSi coating is to prevent the formation of oxide scale (mainly Fe oxide) on the surface of the steel sheet during the heating process of hot stamp forming. Therefore, it is preferred to apply the coating on both sides of the steel sheet. The content of Al component in the Al coating is 70 wt% or more, while the contents of other elements are not particularly limited.
[0071] In addition to Al, the AlSi coating used in this embodiment also contains silicon (Si). Si forms tough phases such as Fe2SiAl7, Fe2SiAl2 and Fe(Al,Si) at the interface between the substrate and the coating during fusion coating, thereby inhibiting the formation of Fe-Al brittle phase at said interface. When the amount of added Si in the coating is less than 5 wt%, the ratio of Fe-Al brittle phase at the interface between the coating and the substrate is high during fusion coating, and cracks penetrating the coating easily form during processing, which damages the corrosion resistance of the processed parts. Furthermore, when the amount of added Si is more than 11 wt%, the corrosion resistance and weldability of the coating are reduced, so the amount of added Si in the AlSi coating is preferably 5-11 wt%.
[0072] In addition to Al and Si, the AlSi coating also contains 2 to 4 wt. % Fe, which dissolves from the equipment and substrate during the plating process of the substrate, and may also contain unavoidable impurity elements such as Zn, Mg, Ca, and Mn.
[0073] The AlSi coating undergoes alloying with Fe in the substrate to various degrees during melting and hot stamping heating. Therefore, the coating does not necessarily consist of layers with uniform composition, and may contain phase-separated layers (alloy layers) with partially different degrees of alloying. The AlSi-coated steel sheet is obtained by immersing a pretreated steel strip into a molten liquid consisting of Al and 5 to 11 mass (weight) % Si on a continuous molten AlSi production line. The coating amount of the AlSi coating on each side of the substrate is preferably 25 to 90 g / m 2 The coating weight is 25g / m 2 When the coating amount is less than 90 g / m, the anti-oxidation effect of the Al or AlSi-based coating described above cannot be sufficiently obtained. 2 When it is more, the surface roughness of the coated steel sheet increases, and the hot stamping heating process is accompanied by the formation of an Al-Fe alloy layer whose surface hardness is high, and the surface roughness further increases, resulting in an increase in the friction coefficient between the steel sheet and the mold during the hot stamp forming process.
[0074] The present invention focuses on a specific composite coating layer formed on the coated steel sheet, and therefore the composition and performance of the coated steel sheet to be used are not particularly limited. The description of the coating of the coated steel sheet is merely exemplary. Users can choose different coated steel sheets for coating according to their actual needs.
[0075] Table 1 lists the mass parts of each component in the solid content of the aqueous surface treatment liquids in Examples 1 to 32 and Comparative Examples 1 to 8. All of the following aqueous surface treatment liquids are used to form a composite coating layer on the surface of a coated steel sheet having an AlSi coating.
[0076] [Table 1-1]
[0077] [Table 1-2]
[0078] [Table 1-3]
[0079] Table 2 shows the results of the coating of the AlSi-coated steel sheets in Examples 1 to 32 and Comparative Examples 1 to 8. The specification, the cure temperature used to form the composite coating, and the dry coat weight of the composite coating are listed.
[0080] [Table 2-1]
[0081] [Table 2-2]
[0082] After the aqueous surface treatment liquid solidified on the surface of the coated steel sheet, a coated steel sheet for hot stamping was obtained. The performance tests of the coated steel sheets for hot stamping in Examples 1-32 and Comparative Examples 1-8 were carried out before and after hot stamping, respectively. The hot stamping method includes the steps of cutting the coated steel sheet for hot stamping described above into a die, heating, and stamp forming. The specific process conditions are listed in Table 3. The die used to stamp form the coated steel sheets for hot stamping in Examples 1-32 and Comparative Examples 1-8 is a flat die with a water-cooling function.
[0083] [Table 3-1]
[0084] [Table 3-2]
[0085] The performance tests of the coated steel sheets for hot stamping were carried out according to the test methods described below. The test results are listed in Table 4 (the following performance tests 1-3 were carried out on the coated steel sheets for hot stamping before hot stamping, and the performance tests 4-9 were carried out on the coated steel sheets for hot stamping after hot stamping).
[0086] 1) Adhesion test of surface coating (before hot stamping) Adhesion test: 3M 610 tape was applied to the surface of the hot stamping coated steel plate, ensuring that the tape was completely adhered to the surface of the steel plate. The tape was then quickly peeled off by using force at an angle of 60° to the surface of the sample. The content of W element or Zn element (comparative example) on the surface of the steel plate before and after the test was determined by using XRF (X-ray fluorescence analyzer) to obtain the remaining amount (mass fraction) of the corresponding element. The meaning of the symbols in the corresponding test results in Table 4 is as follows: ◎(Excellent): 95-100% remaining ○(Good): 80-94% remaining △(Medium): 50~79% remaining × (bad): Remaining amount < 49%
[0087] 2) Solvent resistance test A fine cloth soaked in 80% by volume ethanol is used to wipe the surface of the hot stamping coated steel sheet back and forth 30 times. The content of W element or Zn element (comparative example) on the surface of the steel sheet before and after wiping is determined by using XRF to obtain the remaining amount (mass fraction) of the corresponding element after wiping. The meaning of the symbols in the corresponding test results is as follows: ◎(Excellent): 95-100% remaining ○(Good): 80-94% remaining △(Medium): 50~79% remaining × (bad): Remaining amount < 49%
[0088] 3) Heat and moisture resistance tests The coated steel sheets for hot stamping were placed in a constant temperature and humidity chamber at 49°C and 98% humidity for 120 hours. The heat resistance and humidity resistance of the coated steel sheets were evaluated based on the surface rust area. The specific evaluation was performed in accordance with ISO-10289: Methods for corrosion testing of metallic and other inorganic coatings on metallic substrates -- Rating of test specimens and manufactured articles subjected to corrosion tests. The symbols in the corresponding test results have the following meanings: ◎(Excellent): Surface rust area ≦5% ○(Good): Surface rust area 5%~10% △(Medium): Surface rust area 11%~50% × (bad): Surface rust area > 51%
[0089] 4) Adhesion test of surface coating (after hot stamping) Adhesion test: 3M 610 tape was applied to the surface of the test sample plate, ensuring that the tape was completely adhered to the surface of the steel plate. The tape was then quickly peeled off by using force at an angle of 60° to the surface of the sample. The content of W element or Zn element (comparative example) on the surface of the steel plate before and after the test was determined by using XRF to obtain the remaining amount (mass fraction) of the corresponding element. The meaning of the symbols in the corresponding test results is as follows: ◎(Excellent): 95-100% remaining ○(Good): 80-94% remaining △(Medium): 50~79% remaining × (bad): Remaining amount < 49%
[0090] 5) Thermal lubricity test The thermal lubricity test of the coated steel plate for hot stamping was carried out using a testing machine for testing the high temperature friction coefficient of the plate strip shown in FIG. 2. A test sample plate 20 of 500 mm×100 mm was welded with a thermocouple and then inserted into a heating furnace 29 and held at 930° C. for 4 minutes. The stepping motor 21 was operated to drive the coupling 22 to pull out the test sample plate 20. When the surface temperature of the test sample plate 20 was lowered to 700° C. as monitored by the recorder 24, a load (load pressure) of 3 MPa was applied to the surface of the test sample plate by a die (the die has a surface area of 10 mm×10 mm and includes an upper die 26 and a lower die 28). The die surface was cooled through a cooling water channel 27 inside the die. The coupling 22 was driven by the stepping motor 21 to pull the test sample plate 20 at a speed of 20 mm / s. The pull-out load was recorded by a force sensor 25. The thermal friction coefficient was obtained according to the formula: Thermal friction coefficient = withdrawal load / (2 x loading pressure x mold surface area). The meanings of the symbols in the corresponding test results are as follows: ◎(Excellent): Thermal friction coefficient ≦0.35 ○(Good): Thermal friction coefficient 0.35~0.4 △(Medium): Thermal friction coefficient 0.4~0.5 × (bad): Thermal friction coefficient > 0.5
[0091] 6) Spot weldability test The test sample plate was cut to a size of 30 mm x 80 mm. The possible current range (the difference between the upper and lower current limits) was measured. The measurement conditions were as follows: the lower current limit was set at a melt diameter of 4.25d. 1 / 2 (where d is the plate thickness). For example, for a plate thickness of 1.4 mm, the lower limit current is 5.0 kA. The upper limit current is defined as the current at which the weld spatter phenomenon first occurs. Electrode: Chromium copper material, DR (Dezincification resistance of brass) type (tip diameter: 6mm, 40R radius) Pressure: 4300N Power-on time: 20 cycles (50Hz) The meaning of the symbols in the corresponding test results is as follows: ○(Good): Available current range ≥ 1.5kA × (bad): Available current range < 1.5kA
[0092] 7) Adhesion test The test sample plate was cut to a size of 25 mm x 100 mm. After the surface of the sample plate was wiped with acetone to remove surface dirt, the sample plate was immersed in anti-rust oil for 3-5 seconds, and then removed from the oil and placed vertically for 24 hours. Next, a structural adhesive having a length of about 13 mm and a thickness of about 0.1 mm (the thickness of the adhesive was determined by adding 10 or less beads to the adhesive area using glass beads with a diameter of 0.1 mm) was applied onto the short side edge of one sample plate covered with oil, and the edge of the other sample plate covered with oil was covered at the adhesive position (the two sample plates were lined up in the width direction). The adhesive bond form of the two sample plates is shown in Figure 3. Then, the two sample plates were fixed with a clamp so that the adhesive bond part remained in the form shown in Figure 3. The part was then heated in an oven at 170 ° C for 20 minutes, and then placed under standard conditions (101.3 kPa; 25 ° C) for 24 hours before testing. The two samples were pulled in opposite directions. For example, sample 1 was pulled in the F1 direction, and sample 2 was pulled in the F2 direction to break the adhesive bond. F1 and F2 were on the longitudinal axis of the sample plate on which they acted, respectively. The tensile forces F1 and F2 were applied by extending the clamps at a pulling speed of 50 mm / min. The failure mode when the adhesive bond broke was recorded (the failure phenomenon of the adhesive joint was evaluated according to GB / T16997-1997 “Adhesives-Designation of main failure patterns”, where CF: failure phenomenon occurring on the main body of the structural adhesive; AF: failure phenomenon where the structural adhesive separates from the bonding substrate surface; PF: failure phenomenon at the adhesive bonding substrate or AlSi coating). The meaning of the symbols in the corresponding test results is as follows: ○ (Good): The failure mode in which the structural adhesive separates from the bonded substrate surface is CF. × (Fail): The failure mode in which the structural adhesive separates from the bonded substrate surface is AF or PF.
[0093] 8) Chemical conversion treatability test After the surface dirt was removed from the test sample plate with an alkaline degreaser (Parkerizing FC-E2032), the test sample was rinsed with pure water and immersed in a surface conditioner (Parkerizing PL-Z) for 30 seconds, and then the test sample plate was transferred and immersed in a phosphating solution (Parkerizing PB-L3020) at 35° C. for 2 minutes. The meanings of the symbols in the corresponding test results are as follows: ○ (Good): Zinc phosphate crystal coating was deposited × (bad): no zinc phosphate crystal coating was deposited
[0094] 9) Corrosion resistance test after coating: After the above chemical conversion process was completed, the test sample plate was coated with 20 μm of electrophoretic paint (Kansai HG-350), and then baked and solidified in an oven at 170° C. for 20 minutes. The coated test sample plate was then subjected to the method specified in the Japanese JASO M610 standard. The coatings were pre-marked with a knife and tested for 180 cycles (60 days). The maximum blister width on one side starting from the scribe line was measured. The meaning of the symbols in the corresponding test results is as follows: ◎(Excellent): Blister width ≦3mm ○(Good): Blister width 3-6mm × (defective): Blister width > 6mm
[0095] [Table 4-1]
[0096] [Table 4-2]
[0097] [Table 4-3]
[0098] The coated steel sheets for hot stamping in Examples 1 to 32 were subjected to the above tests, and the evaluation results were The results are all "◎" and "○", and it can be seen from Table 4 that the coated steel sheets for hot stamping containing the composite coating layer have excellent or good comprehensive properties in terms of solvent resistance, corrosion resistance, high-temperature lubricity, weldability, adhesion and coatability after hot stamping.
[0099] By combining Table 1 with Table 4, it can be seen that, compared with Examples 1-32, due to the low content of aqueous anionic polymer resin A in the surface treatment agent of Comparative Examples 1-3 and 8, the film-forming properties of the applied aqueous surface treatment solution after drying are poor, and the adhesion, solvent resistance and corrosion resistance of the composite coating layer are poor. Furthermore, in Comparative Examples 4 and 7, there is no tungsten-containing compound B, so there is no tungsten oxide compound with high-temperature lubrication function in the hot stamping process, resulting in poor high-temperature thermal lubricity. In Comparative Example 5, the amount of boron-containing compound D added is low, and the mass ratio (W) of elemental zinc (Zn) and boron (B) is low. Zn / W B ) reaches 10,000, and the zinc-containing compound C does not form a good bond with the coated steel sheet during the heating stage of the hot stamping process, and a loose zinc oxide layer forms on the surface of the coated steel sheet, resulting in poor weldability and adhesion of the resulting coated steel sheet for hot stamping. In Comparative Example 6, the amount of boron-containing compound D added is too large, and the mass ratio (W Zn / W B ) is 50, the boron-containing compound D affects the formation of zinc phosphate crystal coating during the chemical conversion treatment after hot pressing, and the corrosion resistance of the coated steel sheet for hot stamping after coating is poor.
[0100] In summary, in the present invention, the surface of the coated steel sheet is coated with an aqueous surface treatment liquid, so that good high-temperature thermal lubricity can be achieved in the hot stamping process, and the processability of the coated steel sheet for hot stamping is improved. Therefore, compared with materials not treated with an aqueous surface treatment liquid, complex deformation forming processing can be achieved, the wear of the surface of the hot stamping die can be reduced, the frequency of die repair can be reduced, and production efficiency can be improved. For the parts after the hot stamping process, good weldability and adhesion can be achieved, the chemical conversion processability is good, and the corrosion resistance after coating is also improved. According to the present invention, the application scope of the hot stamping process of the coated steel sheet for hot stamping is expanded, and the applicability of the related parts in the automobile industry and the machining industry is also improved.
[0101] It should be understood by those skilled in the art that the above embodiments are merely illustrative of the present invention and are not intended to limit the present invention. Any changes and modifications to the above embodiments within the spirit of the present invention will fall within the scope of the claims of the present invention.
Claims
1. A coated steel sheet for hot stamping, the coated steel sheet for hot stamping comprising a coated steel sheet and a composite coating layer formed by applying an aqueous surface treatment liquid onto the coated steel sheet; The coated steel sheet includes a substrate and an Al or AlSi-containing coating formed on one or both sides of the substrate; The composite coating layer comprises an aqueous anionic polymer resin A, a tungsten-containing compound B, a zinc-containing compound C, a boron-containing compound D, a water-soluble thickener E and an aqueous surface improvement aid F.
2. The composite coating layer is 1 to 5 g / m 2 2. The coated steel sheet for hot stamping according to claim 1, having a dry coating weight of
3. The coated steel sheet for hot stamping according to claim 1, wherein the composite coating layer comprises the following components in parts by mass: Aqueous anionic polymer resin A: 15 to 65 parts, preferably 20 to 50 parts; Tungsten-containing compound B: 10 to 40 parts, preferably 15 to 35 parts, by weight of tungsten element; Zinc-containing compound C: 3 to 15 parts by mass of zinc element; Boron-containing compound D: 0.004 to 0.03 parts, preferably 0.01 to 0.03 parts, in terms of parts by mass of boron element; Water-soluble thickener E: 0.01 to 0.5 parts, preferably 0.1 to 0.4 parts; Aqueous surface improving agent F: 0.5 to 2 parts, preferably 1 to 1.5 parts.
4. 2. The coated steel sheet for hot stamping according to claim 1, wherein the substrate comprises the following components in mass %: C: 0.20-0.25 wt %, Si: 0.01-0.4 wt %, Mn: 1.0-1.4 wt %, Ti: 0.02-0.05 wt %, B: 0.001-0.005 wt %, and the balance being Fe and other inevitable impurities; and / or the Al-containing coating contains 70 wt % or more Al; and / or the AlSi coating contains 5-11 wt % Si.
5. An aqueous surface treatment liquid for forming the composite coating layer according to any one of claims 1 to 4, An aqueous surface treatment solution, the solid phase material comprising the following components in parts by weight: Aqueous anionic polymer resin A: 15 to 65 parts; Tungsten-containing compound B: 10 to 40 parts by mass of tungsten element; Zinc-containing compound C: 3 to 15 parts by mass of zinc element; Boron-containing compound D: 0.004 to 0.03 parts, preferably 0.01 to 0.03 parts, in terms of parts by mass of boron element; Water-soluble thickener E: 0.01 to 0.5 parts, preferably 0.1 to 0.4 parts; Aqueous surface improving agent F: 0.5 to 2 parts, preferably 1 to 1.5 parts.
6. the aqueous anionic polymer resin A is one or more selected from aqueous acrylic resins, aqueous epoxy resins, aqueous polyester resins and aqueous alkyd resins; and / or the tungsten-containing compound B is one or more selected from tungsten oxide, tungstate or tungsten metal salt; and / or the zinc-containing compound C is selected from zinc oxide, a zinc salt or an organozinc compound; and / or The boron-containing compound D is selected from boron oxide, a borate salt, or an organic boron compound. and / or the water-soluble thickener E is one or more selected from water-soluble hydroxymethylcellulose, water-dispersible alkali-swellable polyacrylic acid emulsion, water-dispersible non-ionic polyurethane associative thickening resin; and / or The aqueous surface improvement aid F is one or two selected from water-dispersible modified polydimethylsiloxane and water-dispersible polyether-modified silicone; and / or the aqueous anionic polymer resin A is 20 to 50 parts by weight; and / or the tungsten-containing compound B is 15 to 35 parts by weight, in terms of parts by weight of elemental tungsten; The aqueous surface treatment liquid according to claim 5.
7. the aqueous anionic polymer resin A has a number average molecular weight greater than 8,000, and the mass fraction of harmful substances resulting from the combustion of said aqueous anionic polymer resin A is less than 1% by weight of the total solids of said aqueous anionic polymer resin A; and / or When tungsten-containing compound B is a water-insoluble tungsten compound, said tungsten-containing compound B has a particle size of 5 to 1,000 nm; and / or When the zinc-containing compound C is a water-insoluble zinc compound, the zinc-containing compound C has a particle size of 5 to 1,000 nm; and / or the mass ratio of elemental zinc in said zinc-containing compound C to elemental boron in said boron-containing compound D is from 150:1 to 750:1, preferably from 250:1 to 670:1; and / or The water-soluble thickener E has a number average molecular weight of 50,000 to 100,000; The aqueous surface treatment liquid according to claim 6.
8. the tungsten-containing compound B has a particle size of 20 to 500 nm; and / or The zinc-containing compound C has a particle size of 20 to 500 nm; The aqueous surface treatment solution according to claim 7.
9. 5. A manufacturing method for the coated steel sheet for hot stamping according to any one of claims 1 to 4, comprising the following steps: applying an aqueous surface treatment liquid onto the surface-cleaned coated steel sheet; and then curing the coated aqueous surface treatment liquid at 80-180°C to form a composite coating layer on the coated steel sheet, thereby obtaining a coated steel sheet for hot stamping.
10. A hot stamping method for the coated steel sheet for hot stamping according to any one of claims 1 to 4, comprising the steps of cutting the coated steel sheet for hot stamping into a die, heating and stamp forming.
11. The hot stamping method according to claim 10, wherein during the heating process, the hot stamping coated steel sheet cut into the mold is heated from 50°C to the final plate temperature and held for 30-60 seconds; and then the heated hot stamping coated steel sheet is transferred to a stamp forming mold having a cooling effect.
12. During the heating process, the average heating rate is 3-12°C / sec and the plate temperature reached is 850-980°C; and / or 12. The hot stamping method according to claim 11, wherein the stamp forming process is carried out in air at a cooling rate of 27°C / s or more before the temperature of the hot stamping coated steel sheet is reduced to 400°C.
13. The hot stamped and formed coated steel sheet has a yield strength of ≥ 950 MPa, a tensile strength of ≥ 1300 MPa, and an elongation after break A of ≥ 5%. 50mm , hardness HV10 ≧400 or A hot stamped and formed coated steel sheet obtainable by the hot stamping method according to any one of claims 10 to 12, having a hardness HRC of 40 and a cold bending angle VDA of ≥ 45°.
Citation Information
Patent Citations
Plated steel plate for hot pressing and hot pressing method of plated steel plate
WO2013122004A1
Al-plated steel sheet, method for hot-pressing al-plated steel sheet, and automotive part
WO2013157522A1
Plated steel sheet for hot stamping and hot-stamped member
WO2021106178A1